motA-mediated flagellar motility modulates biofilm formation and competitive nodulation in Mesorhizobium ciceri USDA 3378 - Chen, Keyu; Hao, Haoran; Zhang, Kaiwen; Li, Ke; Li, Youguo; Andrews, Mitchell; Zhang, Hua; Feng, Zhiqiang; Zhang, Junjie (Frontiers in Microbiology, 2026)
The introduced rhizobial inoculum M. ciceri USDA 3378 demonstrates a significant competitive advantage over the indigenous M. muleiense CCBAU 83963 for nodulating chickpea in newly established planting areas in China. Previous genomic analyses revealed that USDA 3378 possesses a greater number of genes related to cell movement and flagella production compared to CCBAU 83963. Transcriptomic analysis indicated that the expression of the flagella-associated gene motA (flagellar motor protein) significantly changed under symbiotic conditions. Although the genome of M. ciceri USDA 3378 contains the motA gene, its biological function within this strain has not been previously reported. In this study, we constructed a motA mutant (ΔmotA-3378) in USDA 3378 using homologous recombination and biparental conjugation methods to assess the differences in bacterial structure, growth, motility, exopolysaccharide synthesis, biofilm formation, and competitive nodulation ability between the wild type and the mutant. Experimental results showed that the ΔmotA-3378 mutant was unable to produce flagella, leading to reduced motility, diminished biofilm formation, and lower exopolysaccharide production. In competitive nodulation with wild-type USDA 3378, the ΔmotA-3378 mutant's nodule occupancy was 40.43 %. Furthermore, its competitive nodulation advantage against CCBAU 83963 decreased from 100 % (achieved by wild-type USDA 3378) to 94.6 %. These findings indicate that the motA gene plays a crucial role in the motility, exopolysaccharide synthesis, biofilm formation, and competitive nodulation ability of M. ciceri USDA 3378.